In a search for potential drug candidates for combating COVID-19: computational study revealed salvianolic acid B as a potential therapeutic targeting 3CLpro and spike proteins. Issue 19 (15th November 2022) - Elmaaty, Ayman Abo; Darwish, Khaled M.; Khattab, Muhammad; Elhady, Sameh S.; Salah, Mohammed; Hamed, Mohammed I. A.; Al‐Karmalawy, Ahmed A.; Saleh, Moustafa M.
Abstract: The global prevalence of COVID-19 disease and the overwhelming increase in death toll urge scientists to discover new effective drugs. Although the drug discovery process is a challenging and time-consuming, fortunately, the plant kingdom was found to have many active therapeutics possessing broad-spectrum antiviral activity including those candidates active against severe acute respiratory syndrome coronaviruses (SARS-CoV). Herein, nine traditional Chinese medicinal plant constituents from different origins (Glycyrrhizin 1, Lycorine 2, Puerarin 3, Daidzein 4, Daidzin 5, Salvianolic acid B 6, Dihydrotanshinone I 7, Tanshinone I 8, Tanshinone IIa 9 ) previously reported to exhibit antiviral activity against SARS-CoV were virtually screened in silico (molecular docking) as potential inhibitors of SARS-CoV-2 target proteins. The tested medicinal plant compounds were in silico screened for their activity against two key SARS-CoV-2 target proteins; 3CLpro, and Spike binding-domain proteins. Among the tested medicinal plant compounds, Salvianolic acid B 6 (Sal-B) showed promising binding affinities against the two specified SARS-CoV-2 target proteins compared to the reference standards used. Hence molecular dynamics simulations followed by calculating the free-binding energy were carried out for Sal-B providing information on its affinity, stability, and thermodynamic behavior within the two SARS-CoV-2 target proteins as well as key ligand-protein binding aspects. Besides, the quantum mechanical calculations showed that Sal-B can adopt different conformations due to the existence of various rotatable bonds. Therefore, the enhanced antiviral activity of Sal-B among other studied compounds can be also attributed to the structural flexibility of Sal-B. Our study gives an explanation of the structure activity relationship required for targeting SARS-CoV-2 3CLpro and Spike proteins and also facilitates the future design and synthesis of new potential drugs exhibiting better affinity and specificity. Besides, an ADME study was carried out on screened compounds and reference controls revealing their pharmacokinetics properties. Communicated by Ramaswamy H. Sarma